Transverse Retropalatal Collapsibility Is Associated with Obstructive Sleep Apnea Severity and Outcome of Relocation Pharyngoplasty. (December 2015) - Chen, Hung-Chin; Lee, Li-Ang; Hsin, Li-Jen; Lin, Wan-Ni; Fang, Tuan-Jen; Huang, Chung-Guei; Li, Hsueh-Yu
Objective: The aim of this study was to investigate whether the retropalatal airway shape and collapsibility defined by awake nasopharyngoscopy with Müller's maneuver were associated with apnea-hypopnea index (AHI), positional dependency, and surgical outcome of relocation pharyngoplasty in patients with obstructive sleep apnea. Study Design: Case series with planned data collection. Setting: Tertiary referral center. Subjects and Methods: A total of 45 obstructive sleep apnea patients were included who underwent conservative treatment (n = 13) or relocation pharyngoplasty (n = 32), and their baseline and postoperative polysomnographies and awake nasopharyngoscopies with Müller's maneuver were reviewed. Shape ratio (transverse diameter [TD] / longitudinal diameter [LD]) in the stationary and Müller's phases and collapsibility (ColTD and ColLD ) of the airway at the level of the uvular base were measured with a picture archiving and communication system. Intra- and interrater reliabilities were assessed. Associations among nasopharyngoscopic measurements, AHI, positional dependency, and surgical success (defined as a reduction of AHI ≥50% and a postoperative AHI ≤20/h) were statistically analyzed. Results: Reliability tests indicated substantial agreements of all nasopharyngoscopic measurements between raters and within raters. A higher baseline ColTD was significantly associated with an elevated AHI ( r = 0.49, P = .001), whereas a lower postoperative ColTD was significantly related to surgical success ( r = −0.38, P = .034). Nasopharyngoscopic findings were not statistically significantly correlated with positional dependency. Conclusion: Transverse retropalatal collapsibility measured by awake nasopharyngoscopy with Müller's maneuver helps to predict individuals with moderate to severe sleep apnea and surgical outcome.